Phytophthora diseases in horticultural crops - Chowdappa, P; Kumar, N K Krishna (Indian Horticulture, 2019)
The Phytophthora is a versatile causal organism, inflicting enormous losses on horticultural crops. The losses due to P. infestans have been estimated to 12 billion per annum. Economic loss from late blight of potato was highest (44% losses) in Sub-Saharan Africa, followed by Latin America, Caribbean (36%), South-East Asia (35%), South-West Asia (19%) and middle-east and North Africa (9%). Average crop loss in India are estimated to be 15% higher. In tomato, fruit infection may range from 41 to 100% in unprotected fields and from 12 to 65% if protected with systemic fungicides. Late blight was an annual threat in northern India prior to 2006, but it was not a major problem on potato or tomato production in south India. Since the 2008 growing season, severe late blight epidemics have occurred on both tomato and potato in Karnataka, Tamil Nadu and Andhra Pradesh, and have often caused 100% crop losses, say the authors.